2015
DOI: 10.1007/s00018-015-2088-7
|View full text |Cite
|
Sign up to set email alerts
|

Novel affinity binders for neutralization of vascular endothelial growth factor (VEGF) signaling

Abstract: Angiogenesis denotes the formation of new blood vessels from pre-existing vasculature. Progression of diseases such as cancer and several ophthalmological disorders may be promoted by excess angiogenesis. Novel therapeutics to inhibit angiogenesis and diagnostic tools for monitoring angiogenesis during therapy, hold great potential for improving treatment of such diseases. We have previously generated so-called biparatopic Affibody constructs with high affinity for the vascular endothelial growth factor recept… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
20
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 19 publications
(22 citation statements)
references
References 40 publications
1
20
0
Order By: Relevance
“…That selection effort yielded two variants that bound human VEGFR2 and were also cross-reactive for murine VEGFR2. After affinity maturation and construction of the biparatopic high-affinity binder (Z VEGFR2 -Bp2), we again confirmed cross-reactivity between human VEGR2 and murine VEGFR2 29 , 30 . The Z VEGFR2 -Bp2 hence binds both orthologs with similar affinity and the affinity measurements presented here are in agreement with the previously published results, indicating a strong position for future clinical translation.…”
Section: Discussionmentioning
confidence: 55%
See 3 more Smart Citations
“…That selection effort yielded two variants that bound human VEGFR2 and were also cross-reactive for murine VEGFR2. After affinity maturation and construction of the biparatopic high-affinity binder (Z VEGFR2 -Bp2), we again confirmed cross-reactivity between human VEGR2 and murine VEGFR2 29 , 30 . The Z VEGFR2 -Bp2 hence binds both orthologs with similar affinity and the affinity measurements presented here are in agreement with the previously published results, indicating a strong position for future clinical translation.…”
Section: Discussionmentioning
confidence: 55%
“…The interaction between NODAGA-Z VEGFR2 -Bp 2 and mVEGFR2 was analyzed using a surface plasmon resonance (SPR)-based biosensor assay to verify that conjugation of the NODAGA chelator had no negative influence on the binding to the receptor. The previously studied Z VEGFR2 -Bp 2 -ABD 30 was included in the assay for comparison. The results from the assay showed similar binding to mVEGFR2 for NODAGA-Z VEGFR2 -Bp 2 compared with Z VEGFR2 -Bp 2 -ABD, which suggested that the NODAGA conjugation did not appreciably affect association/dissociation of the interaction ( Figure S1 ).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…58 In addition, the resulting biparatopic molecule blocked ligand receptor interaction and inhibited angiogenic sprout formation of endothelial cells as efficiently as the antibody ramucirumab, which is approved for treatment of metastasized lung, colorectal and gastric cancer. 59 This suggests that Affibody molecules could be used for therapeutic intervention, and will be discussed below.…”
Section: Early Stage Imaging Agentsmentioning
confidence: 99%